2010
DOI: 10.1108/01425451011051622
|View full text |Cite
|
Sign up to set email alerts
|

Direct participation quality and organisational commitment: the role of leader‐member exchange

Abstract: Purpose -The relationship between participation quality and commitment has received relatively limited attention in the industrial relations (IR) and human resource management (HRM) literature. This paper seeks to fill some of the gaps in prior research. It aims to answer three questions: How do participation justice and satisfaction influence affective and normative organisational commitment? Does leader-member exchange (LMX) influence satisfaction and perceived justice with participation? Do the three assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…Consistent with previous research, PSS plays a crucial role as a promoter of employee participation in organizations. These results lend further support to the notion that employees feel supported by managers when they encourage them to participate in the decision-making process (Wayne et al, 2002; Torka et al, 2010; Park, 2015). Evidence from this study confirms that the so-called dyad gender composition of both managers and employees has an effect on participation (Ayman et al, 2009).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Consistent with previous research, PSS plays a crucial role as a promoter of employee participation in organizations. These results lend further support to the notion that employees feel supported by managers when they encourage them to participate in the decision-making process (Wayne et al, 2002; Torka et al, 2010; Park, 2015). Evidence from this study confirms that the so-called dyad gender composition of both managers and employees has an effect on participation (Ayman et al, 2009).…”
Section: Discussionsupporting
confidence: 73%
“…In high LMX, supervisors create social exchanges with trust, whereas lower LMX is featured by a minimal level of support. Previous researchers observe that this supervisor-subordinate combination has a positive impact on employee involvement in participation (Torka et al, 2010).…”
Section: Literature Review and Hypothesismentioning
confidence: 79%
“…In addition, research among nurses has shown that promotional opportunities, career development and lifelong learning activities promote job satisfaction and increased retention [6,69]. A similar positive effect has been found for organizational responsibilities and empowerment on intention to quit, as employees feel more valued by being given responsibilities [70,71]. …”
Section: Introductionmentioning
confidence: 85%
“…Employees who are valued by being given responsibilities and trust, usually feel motivated, resulting in reduced employee turnover and an increased employee retention (Liou and Cheng, 2010). Employees who feel un-recognised, un-trusted, are punished for minor mistakes, are subjected to strict checking of work done, would consider the work environment as an unfavourable organisational climate (Toka et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%